A New Method for the Rapid Polymerization of Hydroquinone Catalyzed by Copper‐ammonia Complexes. Issue 15 (17th April 2023) - Liu, Mengyu; Yu, Xiang; Yang, Lanting; Nong, Guangzai
Abstract: Poly(hydroquinone) (PHQ) is a class of polymers with a leading chain composed entirely of quinone‐phenol structures, which possess both the heat resistance of polymers and the redox activity of the monomer quinone‐phenol and have promising applications in sensors, anti‐corrosion and antioxidants. However, the current synthesis efficiency is low, and the product solubility is poor, which hinders its wide application. In this paper, the copper‐ammonia complex was used to catalyze the polymerization of hydroquinone. The product's structure was verified by FTIR, UV‐Vis, XPS, SSNMR and EDS. The degree of PHQ obtained by GPC was 2–9, and the reaction mechanism of the polymerization process was demonstrated in detail. The experiments showed that the copper‐ammonia complex not only acted as a catalyst but also participated in the reaction, firstly generating the PHQ copper‐ammonia complex, which is almost insoluble in water and common organic solvents. Then by further acid washing to dislodge the copper‐amino groups, the resulting PHQ was able to dissolve in solvents such as DMSO and methanol. In addition, the method is three times faster than the catalytic rate using an equivalent amount of ammonia. Abstract : In this study, copper‐ammonia complexes were utilized as catalysts for the polymerization of hydroquinone. These complexes not only acted as catalysts, but also bound to the poly(hydroquinone) during the polymerization process. With acid hydrolysis to remove the complexes, a thermally stable poly(hydroquinone was obtained with a degree of polymerization of 2–9 and yield of 63.2 %. The copper‐ammonia complexes also accelerated the polymerization rate by three times compared to using only ammonia solution, offering potential for improving hydroquinone polymerization efficiency.